Impact of Teachers' Training on Students' Learning Attitude and Organisational Behavior - Atteeq Razzak,; Muhammad Adeel,; Sabrina Agha,; Rao, Gazal (JCTE, 2024)
Enhancing the performance and productivity of the instructors has always been a focus of Training and development. An institution's Training and development program is a real effort to give instructors the chance to get familiar with a range of abilities, knowledge, attitudes, and behaviors. The education sector needs to become more adept at using technology, being dynamic and up to date to meet the ever-growing demands of the current educational system. To elevate this educational sector to the heights of worldwide standards, there is always a need for talented and skilled labor. This study examines how instructors' Training affects students' learning and, as a result, organizational performance. The sample was taken from teachers, head teachers, and school heads. This study employs quantitative research methodology. Random techniques were used in the collection of data. For this research, 100 questionnaires were delivered to the teachers and heads of different schools, i.e., the primary, middle, and high groups of various schools. The data were analyzed in SPSS 19 using multiple descriptive and correlation techniques. This research enables us to conclude that we can shape students' learning abilities and critical thinking skills through teachers' Training. As a result, the whole performance of organizations can be improved. Teacher training should be conducted in keeping with the latest trends so that students and Organizations can